Self-determination in Health Care: A Multiple Case Study of Four First Nations Communities in Canada - Mashford-Pringle, Angela Rose
The perceived level of self-determination in health care in four First Nations communities in Canada is examined through a multiple case study approach. Twenty-three participants from federal, provincial and First Nations governments as well as health care professionals in the communities of Blood Tribe, Lac La Ronge, Garden Hill and Wasagamack First Nations provided insight into the diversity of perception of self-determination in First Nations health care. The difference in definition between Aboriginal and the federal and provincial governments is a factor in the varying perceptions of the level of control First Nations communities have over their health care system. Participants from the four First Nations communities perceived their level of self-determination over their health care system to be much lower than the level perceived by provincial and federal government participants. The organization and delivery of health care is based on the location of the community, the availability of the human resources, the level of communication, the amount of community resources, and the ability to self-manage. The socio-political history including impact of contact, residential schools, and integration of Aboriginal worldview are factors in the organization and delivery of health care as well as the perceived level of self-determination that the community sees. The duration and intensity of contact influences how health care is organized as the communities become more familiarized with the biomedical model that most Canadians use. Having a holistic health care system that includes acknowledging the socio-political history, culture, language, worldview and traditional medicines is important to the four First Nations communities, but this has not been fully embraced in any of the communities. Despite their differences, all four communities are working toward self-determination that hopefully would result in an ‘ideal’ First Nations health care system which is holistic, cultural, spiritual, and interdisciplinary and ultimately lead to full management of the health care system. PhD